Characteristics of diffuse retinal nerve fiber layer defects in red-free photographs as observed in optical coherence tomography en face images - Lim, Abegaile Bartolome; Park, Ji-Hye; Jung, Jae Hoon; Yoo, Chungkwon; Kim, Yong Yeon (BMC ophthalmology, 2020)
Backgroud To determine whether diffuse retinal nerve fiber layer (RNFL) defects, identified on red-free fundus photographs, could be identified on optical coherence tomography (OCT) en face structural images and to evaluate which factors are related to the different recognition patterns on en face images. Methods This retrospective, cross-sectional study included open-angle glaucoma eyes with diffuse RNFL defects in the inferior hemifield, identified in red-free photographs. The corresponding OCT en face structural images were divided into 3 groups: (1) no defect, (2) localized defect, and (3) diffuse defect. We compared the demographic and clinical ocular characteristics among the groups. Results A total of 209 eyes from 157 patients were included. The distribution of OCT en face images was: no defect, 25 eyes (11.96%); localized defect, 106 eyes (50.72%); diffuse defect, 78 eyes (37.32%). Logistic regression analysis revealed that eyes with greater mean deviation ( P = 0.004) and thicker inferior RNFL ( P = 0.008) would be included in the no defect and localized defect groups based on OCT en face images, rather than in the diffuse defect group. Conclusion Around half of diffuse RNFL defects identified in the red-free photographs appeared as localized defects in OCT en face images. Mild glaucomatous damage was related to no defect and localized defect groups, classified based on the OCT en face images, in eyes with diffuse photographic RNFL defects. OCT en face images may be helpful in further assessing diffuse RNFL defects seen in red-free photographs in eyes with open-angle glaucoma.